CARACTERIZAÇÃO DE VIDROS TELURITOS DOPADOS COM NANOPARTICULAS DE Ag@PVP E AgNO3@PVP SEM E CO-DOPADAS COM Tb3+ - GOMES, Leonardo Moreira e Silva,; CAPIOTTO, Adriana do Carmo,; LIMA, Sandro Marcio,; ARRUDA, Gilberto José, (ANAIS DO ENIC, 2023)
-